Home alone 3 - Columbus, Chris (Pasig City : Viva Video, 1998)
The fate of the free world hangs in the balance, but the forces of evil are about to meet their match- and he's only eight years old! From comedy legend John Hughes comes this hilarious, action-packed film for the entire family, Home Alone 3. A band of international crooks have hidden a stolen, top-secret computer chip inside a toy car, but an airport mix-up lands it in the hands of whiz-kid Alex Prurrt (Alex D. Urn) who's home alone with the chicken pox in a quite Chicago suburb. When the criminals zero in on Alex's house with their high-tech gadgetry, madness and mayhem kick into high gear as the print-sized hero defends his house against the bumbling bad guys- armed with an array of ambushes and booby traps.